The expression of immunohistochemical biomarkers PAX8 and CD117 in platinum resistant ovarian cancer at Saiful Anwar General Hospital, Malang, Indonesia - Robby Rinaldi Widodo; Tatit Nurseta; Edy Mustofa; Onni Dwi Arianto; R. A. Rose Khasana Dewi (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS